The Perfect Storm for Teacher Education Research in English Universities: The Tensions of Workload, Expectations from Leadership and Research - Aimee Quickfall; Philip Wood (Education Sciences)
In this paper, we report on data from our survey of the university Initial Teacher Education (ITE) sector in England, concerning responses to questions about perceptions of workload and research. Our survey collects responses annually (since 2021) from approximately 12% of the cohort, and includes questions on a variety of topics, with Likert scale and text responses. Here, we report on three interconnected areas with potential impacts on the future of teacher education in England, and with pertinent findings for other nations, including research expectations and opportunities, workload, and the extent to which university leaders understand ITE. Our data show that academics working in ITE face high workloads, and importantly, very little time for research, and in some cases, low expectations from their institutions in terms of their research output. We compare this picture with systematic review findings about the predominantly insider research nature of ITE research in England, and implications for a sector that has no time, energy, or opportunity to carry out research on their own practice and experience. We consider the impact of these patterns for teacher educators’ work and the longer-term sustainability of individuals, the sector, and the research evidence for teacher education.